Prediction of nitrous oxides emissions for remote sensed images and a prognosis of emissions data in agriculture and forestry - Mohamed Nazeem, Mohamed Ayoob (2024)
Land use activities such as agriculture and forestry have a significant impact on greenhouse gas emissions, but these impacts are often underestimated. This is because agriculture and forestry sectors cover a large land area, making on-ground surveys difficult to scale, expensive, and time-consuming. While there have been localized examinations of urban and industrial domains, it remains unclear how agriculture and forestry sectors would fare in a global examination using modern tools such as hyperspectral cameras.